2023
DOI: 10.3991/ijim.v17i02.34293
|View full text |Cite
|
Sign up to set email alerts
|

Digital Didactical Design: The Role of Learning Obstacles in Designing Combinatorics Digital Module for Vocational Students

Abstract: Many changes occur in the world of education as a result of technological advancement, including the compilation of a module. Digital modules that students can easily access and that have been compiled based on an analysis of student learning obstacles are required. Therefore, this research aims to develop a digital module based on student learning obstacles and it employs the theory of Digital Didactical Design (DDD). DDD contains components of learning objectives, learning activities, process-based assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several previous studies have elucidated the topic of digital modules as a form of instructional material based on digital technology. Various prior studies, such as the findings by Nopriana et al (2023) and , revealed that digital modules effectively enhance mathematics learning. However, secondary school students need help in implementing these digital modules.…”
Section: Introductionmentioning
confidence: 96%
“…Several previous studies have elucidated the topic of digital modules as a form of instructional material based on digital technology. Various prior studies, such as the findings by Nopriana et al (2023) and , revealed that digital modules effectively enhance mathematics learning. However, secondary school students need help in implementing these digital modules.…”
Section: Introductionmentioning
confidence: 96%
“…The diagnosis aims to enhance students' mathematical understanding and facilitate the development of individualized didactical design (Larrain & Kaiser, 2022;Wijaya et al, 2019). Furthermore, diagnosing students' learning obstacles is a strategic move in teachers' reflective practice in planning didactic situations and anticipating students' responses (Nopriana et al, 2023;Puspita et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, research on mathematics learning obstacles seems to be primarily concerned with locating empirical evidence of the learning obstacle of students or college students when studying a mathematical topic. Some examples of such mathematical topics are fractions (Isnawan et al, 2022), trigonometry (Maknun et al, 2022), geometric transformation (Kandaga et al, 2022), rational numbers (Novita et al, 2022), derivatives (Puspita et al, 2022), combinatorics (Nopriana et al, 2023) and others. A Marfuah / Mathematics Teachers' Interviewing Strategies for Diagnosing Students' Learning Obstacles study focussing on the abilities of prospective mathematics teachers in analyzing students' learning obstacles (Jatisunda et al, 2022).…”
Section: Introductionmentioning
confidence: 99%